Desain PLTS Off-Grid Dengan Teknologi Penyimpanan Energi Pumped Storage Di Mahakam Ulu - Muhamad Cahyo Samudro; Widodo Pudji Muljanto; Irmalia Suryani Faradisa; Sotyohadi (Indonesian Society of Applied Science (ISAS), 2025)
This research presents the design of an off-grid Solar Power Plant (PLTS) integrated with pumped storage energy technology in Mahakam Ulu Regency, East Kalimantan, as a sustainable energy solution for remote regions. The main objective of this study is to develop a reliable, efficient, and environmentally friendly power generation system by utilizing local renewable energy potential. The research methodology includes identifying 24-hour load demand, analyzing PLTS capacity based on solar radiation potential, calculating hydrological parameters such as water head and flow rate, and determining the capacity and dimensions of key components, including turbines, penstock pipes, pumps, inverters, and storage reservoirs. The technical data show a reservoir volume of 566,784 m³, a head height of 100 meters, a penstock diameter of 1.9 meters, a PLTS capacity of 10.3 MWp using 13,734 solar panels, and a 15 MW inverter. The analysis results indicate that the designed system can maintain continuous electricity supply during nighttime or low-solar conditions through stored potential energy utilization. This configuration significantly reduces dependency on diesel generators, decreases carbon emissions, and supports the national clean energy transition agenda. The off-grid PLTS design integrated with pumped storage technology is proven to be a feasible and sustainable approach that can serve as a reference for developing similar renewable energy systems in other isolated 3T regions with comparable geographical and natural characteristics.